BOUNDEDNESS OF PSEUDO-DIFFERENTIAL OPERATOR FOR S0 CLASS - HABIBURROHMAN (NIM: 20116001), MUHAMMAD
Pseudo-differential operator in a function space is obtained from the Fourier transform of this function space with a multiplier function. This thesis will discuss and prove the boundedness of pseudo-differential operator in Lebesgue space with the multiplier function is in the S0 class.